Development and Evaluation of Novel Water-Based Drug-in-Adhesive Patches for the Transdermal Delivery of Ketoprofen - Kwanputtha Arunprasert; Chaiyakarn Pornpitchanarong; Theerasak Rojanarata; Tanasait Ngawhirunpat; Praneet Opanasopit; Porawan Aumklad; Prasopchai Patrojanasophon (MDPI AG, 2021)
The objective of this study was to develop novel water-based drug-in-adhesive pressure-sensitive adhesives (PSAs) patches for the transdermal delivery of ketoprofen, employing poly(N-vinylpyrrolidone-co-acrylic acid) copolymer (PVPAA) and poly(methyl vinyl ether-alt-maleic anhydride) (PMVEMA) as the main components. The polymers were crosslinked with tartaric acid and dihydroxyaluminium aminoacetate using various polymer ratios. Ketoprofen was incorporated into the PVPAA/PMVEMA PSAs during the patch preparation. The physicochemical properties, adhesive properties, drug content, release profile, and skin permeation of the patches were examined. Moreover, the in vivo skin irritation and skin adhesion performance in human volunteers were evaluated. The patches prepared at a weight ratio of PVPAA/PMVEMA of 1:1 presented the highest tacking strength, with desirable peeling characteristics. The ketoprofen-loaded PVPAA/PMVEMA patches exhibited superior adhesive properties, compared to the commercial patches, because the former showed an appropriate crosslinking and hydrating status with the aid of a metal coordination complex. Besides, the permeated flux of ketoprofen through the porcine skin of the ketoprofen-loaded PVPAA/PMVEMA patches (4.77 ± 1.00 µg/cm2/h) was comparable to that of the commercial patch (4.33 ± 0.80 µg/cm2/h). In human studies, the PVPAA/PMVEMA patches exhibited a better skin adhesion performance, compared with the commercial patches, without skin irritation. In addition, the patches were stable for 6 months. Therefore, these novel water-based PSAs may be a potential adhesive for preparing drug-in-adhesive patches.